Detection of SV40 in colon cancer: a molecular case-control study from northeast Italy. - Campello, Cesare; Comar, Manola; Zanotta, Nunzia; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2010)
To explore the involvement of the simian polyomavirus SV40 in human colon cancer, a molecular case-control study was undertaken in patients and in their relatives living in an area where the spread of SV40 has already been documented. From 2006 to 2008, 94 colon cancer patients (age: 37-90 years) and 91 subjects (age: 32-70 years) relatives of each index case were enrolled. A blood sample and a specimen of cancer tissue or biopsy were collected, from each patient or control, respectively. Samples were analyzed twice for Polyomavirus (i.e., SV40, JCV, and BKV) by PCR and by quantitative real-time PCR (RT-qPCR) with reproducible results. No BKV/JCV was detected either in normal or pathological tissues. SV40 was not present in control subjects, either normal tissue or in biopsies from adenomas or polyps. All blood samples were negative. Conversely, six adenocarcinoma specimens were positive for SV40 sequences (overall prevalence 6.4%, P = 0.03 in comparison with controls). Nevertheless, the SV40-associated colon cancer risk proved statistically not significant (OR = 3.91; P = 0.115) when adjusted for age. Quantitation of SV40 DNA performed by RT-qPCR showed a low viral load ranging from 6.2 x 10(1) to 9 x 10(3) copies per reaction. This molecular case-control survey showed, for the first time in fresh samples and by RT-qPCR, that SV40 can be detected in colon cancer tissue. However, the finding was not statistically significant when compared with a well-structured community control group. Thus, the role of SV40 and other polyomavirus in colon cancer genesis deserves further investigation.
Keywords: Adenocarcinoma; Adult; Aged; Aged, 80 and over; BK Virus; Case-Control Studies; Colonic Neoplasms; DNA, Viral; Female; Humans; Italy; JC Virus; Male; Middle Aged; Polymerase Chain Reaction; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections